(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The study aimed to determine the role of the internal marketing strategy with its dimensions (internal training, employee motivation, employee empowerment, and internal interaction) in achieving sustainable development for air transport companies. The researcher relied on the deductive approach as a general approach to the research, and followed the survey methodology. The research sample was 151 Individual of the company’s staff, and then the researcher conducted a field study for the purpose of clarifying this relationship. The study concluded that the internal marketing strategy in its various dimensions (internal training, employee motivation, employee empowerment, internal interaction) has a role in improving sustainable development. The study recommended that the company should increase its interest in the internal marketing strategy because it will achieve sustainable development in its resources by achieving profits using fewer resources and providing services at lower costs..